TABULASI GAS RUMAH KACA KOTA KEDIRI - Lisanudin Rahman; Mohammad Razif (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
Problems related to GHG emissions (Greenhouse Gases) mainly due to carbon dioxide (CO2) gas causing climate change and global warming. Indonesia is committed to reducing GHG by 26% by 2020. This is realized by the GHG inventory conducted in East Java. The city of Kediri is regionally surrounded by Kediri Regency, where the City of Kediri only has 3 (three) Districts with the largest potential for the tobacco industry with the largest cigarette factory in Indonesia, so that the City of Kediri is used as a reference for the Industrial City area. The sectors that have the largest GHG contribution are industry and transportation. The purpose of this study was to determine the value of FES (Specific Emissions Factor). The determination of FES is used as the basis for calculating the emission tabulation in the Kediri City area. The method used in this research is survey and calculation. The basis for calculations is from the IPCC (Intergovernmental Panel on Climate Change) and the Ministry of Environment (KLH). The emission calculation tabulation uses the approach of fuel consumption. The tabulation results of CO2 Greenhouse Gas Emissions in the City of Kediri from the transportation sector is 11948103.1 kg/year, from the industrial sector it is 2.83533 x 1012 kg/year and from the residential sector it is 7.608494500 x 109 kg/year. So that the total CO2 Greenhouse Gas emission in Kediri City from the three sectors is 2.84306 x1012 kg/year. The results of tabulation of total greenhouse gas emissions show that the highest emissions are in Semampir Village. For the area with the lowest tabulation of greenhouse gas emissions, Blabak Village.